SEVERE CONSTRICTED HEAD – AN EXTREME FORM OF CROUZON SYNDROME POSING CHALLENGING FRONTO-ORBITAL ADVANCEMENT: A CASE SERIES REPORTS - Ciptomurti Lupitasari; Lobredia Zarasade; Magda Rosalina Hutagalung (Jurnal Rekonstruksi dan Estetik)
Highlights: